A DIMENSÃO LÚDICA DA LINGUAGEM CORPORAL INFANTIL E SUA RELAÇÃO COM O PROCESSO DE APRENDIZAGEM: uma reflexão a partir das práticas escolares percebidas nas escolas da rede pública de ensino no município de Imperatriz-MA - Miranda, Amanda Ribeiro (2007)
The present paper consists of a study about the playful dimension of the infantile corporal language and their implications for the learning process. It proposes an analysis concerning the school practices found in the schools of the public teaching network in the municipal district of Imperatriz-MA, and, considering their social determinant. It was based essentially on the theorization found in the area of education and physical education, above all the ones that intend an investigation of the construction of the body concept and of the relationship body/education, in the perspective of the learning, taking into account a historical and cultural approach. In this regard, one has fetched in Merleau-Ponty s contributions, in his work Phenomenology of Perception , as well as from his interlocutors, the necessary theoretical outpouring to the development of this study. The paper shows the evidence, starting from observations, analysis of documental sources and depositions of the subjects involved in the research, which the affirmation process of the playful dimension of the corporal language, along the learning process, is found weakened due to the observed conditions and that such conditions were revealed disjointedly, considering a pedagogical and social project which considers the body as synthesis of the human totality and, therefore, indispensable element to the process of the human being's formation. It was observed how the decisive factors involve elements that rise from the conditions of the physical space and its use, to the dimension which concerns the involved teachers' graduation. It rises by the complexity of this process, as well as by their determinant, that there is a historical impediment marked by the denial of the body in the school environment, based upon the objectivity of the technical rationality, incorporated by the school. Such impediment needs to be contemplated and overcome, in the sense of moving forward towards a qualitatively better process, which considers the possibility of development of elements related to the human sensibility, which implicates indeed in the process of rescuing the subjectivity, as possibility of overcoming the dichotomy body/mind. It consists in the evidence that in the observed schools such a movement is far away from being rendered, since not only the teachers, but also the educational system itself, does not have the necessary understanding about the relevance of this discussion for the learning process, nor even as well they are recognized as protagonist subjects of this process. Finally, it indicates that the revealed conditions bring about serious implications to the learning process, considering the possibility of an integral education that has as reference the body-subject conception for the educational process, to the detriment of the hegemonic conception of body-machine.